Testing a portion of the Oklahoma aging inmate forgiveness model - Randall, G. Kevin (Journal of religion, spirituality & aging, 2021)
The study tested a portion of the Oklahoma Aging Inmate Forgiveness Model predicting religiosity would be positively and significantly associated with the mediator, forgiveness (self, other, and situation), and the mental health outcome, valuation of life. Further, the study asked, “Does crime type moderate the relationships in the model?” Cross-sectional data from 249 older male inmates affirmed that religiosity and forgiveness matters for participant mental health. Discussion focuses on the fact that not one size fits all. Inmates and their unique backgrounds, crime type, and various assessments, present opportunities for needed psychological, religious, and forgiveness involvement, training, and therapeutic intervention.